Culture change in India :Identity and Globalization - Singh, Yogendra (Jaipur Rawat Publication, 2000)
Culture Change in India: Identity and Globalization offers a critical evaluation of changes in cultural values, institutions and ideologies which constitute India's response to the contemporary challenges from the forces of cultural and economic globalization. In the backdrop of discussions of conceptual and theoretical issues in the study of culture and its processes of change, it evaluates the significance of the present social structure of the Indian society, its historical past and contemporary processes in defining the boundaries and directions of the changes in its cultural systems, whether at the level of locality, region, nation or civilization. It is argued that the unique quality of this relationship between culture and social structure in India, and its adaptive dynamism to meet with new cultural challenges, has provided it resilience to preserve its cultural identity. The book mainly concerns with changes in cultural styles through exposure to global cultural patterns. It also examines the impact of electronic media, migration and increased pace of inter-cultural interactions upon local, regional and national levels of culture. It deals with how these processes have led to the rise in popular culture, changes in the form and style of leisure activities, given rise to new normative standards for defining community relationships, political leadership and generally how it reflects upon India's ability in the future to maintain cultural and social resilience to face up to the new challenges of modernization and globalization.
Keywords: Globalization